2022
DOI: 10.3390/su142114420
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Model Attention Fusion Multilayer Perceptron Prediction Method for Subway OD Passenger Flow under COVID-19

Abstract: At present, machine learning has been successfully applied in many fields and has achieved amazing results. Meanwhile, over the past few years, the pandemic has transformed the transportation industry. The two hot issues prompt us to rethink the traditional problem of passenger flow forecasting. As a special structure embedded in the machine learning model, the attention mechanism is used to automatically learn and calculate the contribution degree of input data to output data. Therefore, this paper uses the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A study in South Korea analyzed the volume of traffic inflow due to the COVID-19 pandemic and also compared the second and third waves (Lee, et al, 2021;Seong, et al, 2021). Various studies are devoted to the prediction of traffic flows in the field of intelligent transport systems in the event of an increase in the number of infected persons during pandemic waves (Li, et al, 2022;Prasse, et al, 2020;Cao & Li, 2022). A study in Spain demonstrated the impact of the COVID-19 pandemic on citizens' mobility during the pandemic, using data from the public transport card system (Rodríguez González, et al, 2021).…”
Section: Assessment Of Traffic Flow Due To the Third Wave Of The Covi...mentioning
confidence: 99%
“…A study in South Korea analyzed the volume of traffic inflow due to the COVID-19 pandemic and also compared the second and third waves (Lee, et al, 2021;Seong, et al, 2021). Various studies are devoted to the prediction of traffic flows in the field of intelligent transport systems in the event of an increase in the number of infected persons during pandemic waves (Li, et al, 2022;Prasse, et al, 2020;Cao & Li, 2022). A study in Spain demonstrated the impact of the COVID-19 pandemic on citizens' mobility during the pandemic, using data from the public transport card system (Rodríguez González, et al, 2021).…”
Section: Assessment Of Traffic Flow Due To the Third Wave Of The Covi...mentioning
confidence: 99%
“…Some scholars have realized that compared with normal passenger flow, abnormal passenger flow fluctuations require more attention for the operation of urban rail transit [9,10].…”
Section: Studies On Passenger Flow Fluctuationsmentioning
confidence: 99%